2014
DOI: 10.1142/s0192415x14500190
|View full text |Cite
|
Sign up to set email alerts
|

Wrist-Ankle Acupuncture for Pain After Transcatheter Arterial Chemoembolization in Patients with Liver Cancer: A Randomized Controlled Trial

Abstract: This study was designed to evaluate the analgesic effect of wrist-ankle acupuncture (WAA) for patients with primary liver cancer (PLC) after transcatheter arterial chemoembolization (TACE). Sixty PLC patients with post-TACE visual analog pain intensity scores greater than 3 were divided equally into two groups receiving either WAA or oral morphine sulphate (MOR) for post-TACE pain. Pain intensity scores were reassessed at 1, 2, 4, and 6 h after analgesic intervention. Patients were also monitored for adverse r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…The analgesics used were IV morphine 8,15,17 and PO oxycodone 8,24 (PO morphine sulfate was used as a control). 23 Studies using PO oxycodone 8,24 after TACE reported an adequate analgesic effect, as defined within these studies. The only available placebo-controlled randomized controlled trial (RCT) 24 reported superior pain control in groups receiving PO controlledrelease oxycodone (CRO).…”
Section: Intravenous or Oral Analgesiamentioning
confidence: 97%
See 2 more Smart Citations
“…The analgesics used were IV morphine 8,15,17 and PO oxycodone 8,24 (PO morphine sulfate was used as a control). 23 Studies using PO oxycodone 8,24 after TACE reported an adequate analgesic effect, as defined within these studies. The only available placebo-controlled randomized controlled trial (RCT) 24 reported superior pain control in groups receiving PO controlledrelease oxycodone (CRO).…”
Section: Intravenous or Oral Analgesiamentioning
confidence: 97%
“…The duration of pain relief for the control group was 4 hours after TACE beyond which the intervention group reported superior analgesic effect. 23 In the 2 DEB-TACEYrelated studies, 15,17 IV morphine was administered 30 minutes before procedure and 6 hours after the procedure. Grades 2 and 3 RUQP was reported in both studies, and Narayanan et al 17 report modification of the pain protocol to include IV hydromorphone at increments throughout the procedure.…”
Section: Intravenous or Oral Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment scheme originates from the principles of WAA and has been practiced in previous clinical trials for several decades [11][12][13][14][15][16][17]. According to the theory of WAA, each side of the body and each limb are longitudinally divided into six zones, and one needling point is defined in each zone at the wrist or ankle.…”
Section: Interventionsmentioning
confidence: 99%
“…No other needling sensation was found. A single registered acupuncturist, with at least 1 year of previous WAA experience, administered the care to all subjects [11,15].…”
Section: Interventionsmentioning
confidence: 99%